Human Resource Factors And Craftsman Productivity In The Creative Industry Of Rumah Atap Konjo - Jusri; Bau Asni; Hasnidar (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
: The local culture-based craft industry is an important part of the creative economy, playing a role in improving community welfare while preserving cultural heritage. However, this industry still faces a major challenge in the form of low artisan productivity. This study aims to analyze the influence of human resource factors, including skills, knowledge, training, work motivation, and working conditions, on the productivity of artisans at the Rumah Atap Konjo in Bulukumba Regency. The study used a quantitative approach with a survey method of 70 artisans, with data analysis using multiple linear regression. The results showed that simultaneously all human resource factors significantly influenced artisan productivity. However, partially, only knowledge and working conditions were proven to have a positive and significant effect on productivity, while skills, training, and work motivation did not show a significant effect. These findings indicate that in the local culture-based craft industry, productivity increases are more determined by cognitive aspects and work environment support than by individual factors that are homogeneous and inherited from generation to generation. This study provides an empirical contribution to the development of human resource studies in the culture-based creative industry and serves as a basis for the formulation of more contextual and sustainable artisan management policies and strategies.